Formulasi Sediaan Masker Gel Peel Off dari Minyak Atsiri Sereh (Cymbopogon citratus): Formulation of the Preparation of Peel Off Gel Mask from Cymbopogon Citratus Essential Oil (Cymbopogon citratus) - Annisa Annisa; Andi Tenri Kawareng; Niken Indriyanti (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Lemongrass (Cymbopogon citratus) is one of the essential oil producing plants known as Lemongrass oil with the main content of citral compounds. Lemongrass essential oil is known to have antioxidant activity. The antioxidant activity of lemongrass oil can be used for skin care in the form of a peel off gel mask. The purpose of this study was to formulate a peel off gel mask preparation from lemongrass essential oil (Cymbopogon citratus) and to know the results of the physical evaluation of the peel off gel mask. The peel off gel mask was made in three formulas with different concentrations of PVA, namely F1 (10%), F2 (13%), and F3 (16%). Physical evaluation tests include organoleptic tests, homogeneity, viscosity, pH, dispersion, and drying time. The peel off gel mask in the three formulas was obtained in the form of a thick gel, white in color, and had a characteristic lemongrass smell. The results obtained based on the physical evaluation showed that the three formulas had met the required standard parameters.